Aplikasi Diagnosa Gizi Buruk Pada Balita Menggunakan Metode Pembobotan (Studi Kasus: Kecamatan Nusaniwe, Kota Ambon) - Grace Apriliany Presilia Kurmasela; Gisela Nina Sevani (Bina Nusantara University, 2015)
The problem of malnutrition in children under five in Sub Nusaniwe Ambon is due to several reasons. Economic problems, lack of knowledge of health problems and lazy to take a child to IHC is a people problem there. In terms of nutrition officers, a problem that occurs is the lack of nutrition officer. This is what can ultimately make the service becomes not optimal. Based on the problems described, it can be used a web-based application that allows one to be developed later. The application store knowledge representation expert or nutritionist toddler, so it can help diagnose malnutrition and nutrient assist officers in performing work optimally, which is represented by the existence of this application. This application uses the inference Forward Chaining, which starts from user input in the form of symptoms experienced, then users give assurance (Certainty Factor) to describe the level of confidence on the symptoms experienced. Output application is whether children under five suffer from malnutrition or the type and value of certainty to be output, advice should intake received toddlers and ways of handling children malnutrition